2017
DOI: 10.1136/heartjnl-2017-311647
|View full text |Cite
|
Sign up to set email alerts
|

Acute chest pain evaluation using coronary computed tomography angiography compared with standard of care: a meta-analysis of randomised clinical trials

Abstract: Compared with other SOC approaches use of CCTA is associated with similar major adverse cardiac events but higher rates of revascularisation in patients with acute chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…There is now increasing evidence to support the use of CCTA over functional ischemia testing in patients with stable chest pain ( 32 , 33 ). Recent trials demonstrated that CCTA clarified the diagnosis of CAD and led to major improvements in patient outcomes by increasing the use of evidence-based preventative therapies ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is now increasing evidence to support the use of CCTA over functional ischemia testing in patients with stable chest pain ( 32 , 33 ). Recent trials demonstrated that CCTA clarified the diagnosis of CAD and led to major improvements in patient outcomes by increasing the use of evidence-based preventative therapies ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors undertook a meta-analysis of RCTs published prior to March 2017 comparing CTCA with standard care in the assessment of patients with acute chest pain 1. Standard care varied across the trials but always incorporated non-invasive functional testing—that is, exercise ECG, stress echocardiography or myocardial perfusion imaging.…”
Section: Methodsmentioning
confidence: 99%
“…They have also shown that CCTA is associated with reduced time to-diagnosis, reduced length of hospital stay and reduced cost 35 , 36 . However, a meta-analysis of the randomized controlled trials in patients with acute chest pain found that there was no difference in the outcomes of all-cause mortality, myocardial infarction or major adverse cardiac events between the CCTA and standard care groups 37 Table 2Randomized controlled trials of CCTA improving outcomes in acute chest pain 35 , 36 , 66 , 67 .ACRIN-PABEACONCATCHCT-COMPARECT-STATNabi et alPERFECTPROSPECTROMICAT-IINumber of patients13684905765626995983954001000CCTA vsStress ECG, stress imagingStress ECG, MPIStress ECG, MPIStress ECGMPIMPIStress echo., MPIMPIStress ECG, Stress echo., MPIAge (mean years)505456525053605754Female (%)544745425456546347Follow-up (months)12119126712121ACRIN-PA, CT Angiography for Safe Discharge of Patients with Possible Acute Coronary Syndromes; BEACON, Better Evaluation of Acute Chest Pain with Coronary Computed Tomography Angiography; CATCH, CArdiac cT in the treatment of acute CHest pain; CT-COMPARE, CT Coronary Angiography Compared to Exercise ECG; CT-STAT, Coronary Computed Tomographic Angiography for Systematic Triage of Acute Chest Pain Patients to Treatment; PERFECT, Prospective Firs...…”
Section: Ccta and Outcomes In Patients With Acute Chest Painmentioning
confidence: 99%